A Comprehensive Examination of Cloud Computing (International Journal of Innovative Research in Computer Science & Technology, 2021)
Cloud computing is a burgeoning  technology that has ushered in a new era by allowing for a  logical computational approach. Over a concept that delivers  on-demand services online, it has revolutionized the  mechanics of IT consumption. Unlike traditional hosting,  cloud services are priced for per basis and may rise or decline  in response to feedback. Such services are typically totally  managed by cloud service providers and demand only a  home computer with an internet connection from users. This  model has got the attention of researchers, capitalists, and  operators in latest days, with most of them presenting a range  of cloud computing, frameworks, and ideas, resulting in a  diversity of definitions, requirements, and models. Despite  the excitement and development in the field, questions  around privacy and security, service discovery partnerships,  sharing of resources, and pricing have created additional  worries about the model's genuine merits. Deny the reality  that infrastructure is predicated on such a 50-year-old  business plan, evidence from this study reveals that this still  needs to expand and overcome present limits that impede it  from fulfilling its full potential. We analyze the top of the  line in cloud applications in this study with the purpose of  uncovering improvements, gaps, and new difficulties.
Keywords: Business Model; Cloud Computing; On Demand; Service Layer Agreement; Virtualization